Sexual and reproductive health knowledge and practices among youth with and without mental illness in Uganda: a comparative study - Emily Tumwakire; Scholastic Ashaba; Vincent Mubangizi; Yahaya Gavamukulya (Tropical Medicine and Health, 2022)
Abstract Background Sexual and reproductive health challenges among youth in low-income countries have persistently remained a public health challenge. In addition to these challenges, approximately 25% of youth experience a mental health illness, a situation anticipated to steeply increase especially in sub-Saharan Africa. However, there is still a scarcity of knowledge on the sexual and reproductive health of youth with mental illness in comparison to youth without mental illness in low-income countries. In this paper, the objective was to compare the sexual and reproductive health knowledge and practices among youth with mental illness and without mental illness at Mbarara Regional Referral Hospital (MRRH), South Western Uganda. Methods Using a cross-sectional comparative study design, 104 youth with mental illness and 101 youth without mental illness were recruited as they sought medical health care services at MRRH. Structured interviews were conducted and they covered sexual and reproductive health knowledge and sexual practices. Results 205 youth were interviewed and of these 53 males and 51 females had mental illness while 49 males and 52 females did not have a mental illness. More youth without mental illness (61.7%) had more knowledge of sexual and reproductive health compared to youth with mental illness (38.3%) with a prevalence odds ratio of 0.29 (CI 0.16–0.52) and p value of 0.001. All youth were knowledgeable about contraceptive methods. Youth with MI engaged more in risky sexual practices though the difference wasn’t statistically significant. Conclusions Youth generally have low sexual and reproductive health knowledge and this was found to be significantly lower in youth with mental illness compared to those without mental illness and they generally tend to engage in risky sexual behavior. It is recommended to incorporate SRH services among the mainstream general youth health care and mental health care services is critical to reducing sexual and reproductive health challenges among youth.